'Thanks to my forced displacement': blackness and the politics of Colombia's war victims. Issue 1 (2nd January 2018) - Cárdenas, Roosbelinda
ABSTRACT: In 1993 Afro-Colombians were granted multicultural rights as members of a distinct ethnic group and as collective subjects of 'black communities'. In recent years, this discourse has intersected with national and international apparatuses that seek to identify victims of Colombia's war in order to grant them rights and reparations. This has resulted in the emergence of a new political subject that is both racialized and defined as a victim: the afro- desplazado, or black Internally Displaced Person (IDP). Using ethnographic description from an urban IDP arrival site in Bogotá, I illustrate how these two discourses have become interwoven in practice and explore their consequences for afro-desplazados . I explore the political limits and possibilities of this new category by showing how Afro-Colombians both adopt it and push at its limits.